Systematic Review On Effectiveness Of Zinc Sulfate In Treatment Of Recurrent Aphthous Stomatitis (Journal of Pharmaceutical Negative Results, 2023)
Background: Zinc sulfate is an inorganic compound used as a nutritional supplement, and it is known to aid in enhancing anti-inflammatory properties. Recurrent aphthous stomatitis is a commonest oral mucosal conditions characterized by painful recurring ulcers. Many current studies focus on establishing Zinc sulfate's potency against Recurrent aphthous stomatitis and its other uses in dentistry as it has anti-inflammatory activity with minimal adverse effects.Aim: To determine the effectiveness of zinc sulfate in the treatment of recurrent aphthous stomatitis.Materials and methods: A systematic review of clinical trials using zinc sulfate as an effective agent against Recurrent aphthous stomatitis. Various databases were searched and obtained a total of 112 articles, among which three studies were included. A systematic review was performed using PubMed, Scholar, Wiley, Cochrane and Science direct. From the total 112 articles that appeared from various sources, 109 articles were screened, and three studies were related to the research topic. This article was reported according to the systematic review guidelines.Result: Three studies were included in the systematic review, of which all are clinical trials showed that Zinc sulfate had a crucial role in reducing inflammation and improving oral hygiene status. The P-value of the three articles selected are 0.001, 0.0001 and > 0.05.Conclusion: With a comparative analysis between the existing related articles about the effectiveness of zinc sulfate in treating the recurrent aphthous stomatitis, the sequel of the effectiveness of zinc sulfate in the treatment of recurrent aphthous stomatitis have to be given.